Improvement of Block Volume Mathematics Learning Outcomes with a Combination of PBL, RME, and TaLKING STICK Models - novitasari (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
This research is motivated by the lack of students' ability to solve problems, students are less involved in the learning process, monotonous learning does not use media, concrete examples and varied models that have an impact on student learning outcomes. The purpose of the study is to describe the activities of teachers and students and analyze student learning outcomes using a combination of PBL, RME, and Talking Stick models. The subjects of the study were 10 students in grade V of SD Muhammadiyah 5 Banjarmasin. The instruments used are observation sheets of teacher and student activities, evaluation sheets. The results of the study prove that teacher activity increased in the first cycle of meeting 1 reaching 83% "Very Good" to in the second cycle of meeting 1 increasing by 100% "Very Good". Student activity in the first cycle of meeting 1 "Less Active reaches 40%" until in the second cycle of meeting 1 increases to 90% "Very Active". Student learning outcomes in the first cycle of meeting 1 reached 30%, in the second cycle of meeting 1 increased to 90%.